Synthesis and Morphology of High Density Barium Zirconate Ceramics - Subramaniam, Selvarajan (2001)
Barium Zirconate (BaZr03) is an inert target material with high resistance to temperature and chemical reaction, which can be used as a crucible. In some literatures, BaZr03 with small particle size is also proposed as material for multilayer capacitors. In this research high dense BaZr03 has been synthesized through a common method, solidstate reaction, where large amount of fine BaZr03 powder can be obtained and further sintered at high temperature to gain high density material. In this study, nitrate precursors were used to lower the formation temperature of BaZr03. The raw materials (Ba(N03)Z and ZrO(N03)z.HzO in 1:1 molar ratio) were calcined at 800De for 8h to obtain a fine and pure BaZr03 crystal. The calcine powder was analysed with X-ray diffraction to confirm that there were no unwanted impurities. The calcined powder was also analysed with laser particle-size analyser and scanning electron microscope to gain more information on the particle sizes and morphology. The low temperature of calcination produced fine powder « lm). Fine powders always facilitate fast boundary diffusion during sintering. Sintering the green pellet between 12000C and 17000C showed vast information of morphology changes. BaZr03 with 0.6!J,m was obtained at 12000C with dwell time of 24h. Further sintering at 16000C for 6h produced a high dense pellet with no or near zero porosity and about 90% density compared to theoretical value. The crystallite size is ranged between 0.36!J,ffi to 0.44!J,ffi. However, the pellets had shrink of about 13%. To prevent the large shrinkage, sintering aids were used. Magnesium oxide (MgO), yttrium oxide (Y203), Aluminium oxide (Ah03), and Barium Stannum oxide (BaSn03) were added up to 5% separately with the calcined BaZr03 powder and sintered between 15000C and 1700oC. Interestingly, with the presence ofMgO, Y203 and Ab03 the sintering shrinkage was reduced to only 2%. Even though there was some level of porosity, BaZr03 with MgO and Y203 pellets with shown about 90% densification.